PENGEMBANGAN BUDAYA TOLERANSI DAN PERDAMAIAN DI AL-ZAYTUN SEBAGAI DASAR KEHIDUPAN BERBANGSA DAN BERNEGARA BERLANDASKAN PANCASILA - bara, Brilliant; Kuat; Basuki; Insanul Haq, Fathan; Ngainnur Rohmah, Siti (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
The development of a culture of tolerance and peace at Al-Zaytun Islamic Boarding School is an important foundation in the life of the Indonesian nation and state based on Pancasila. Al-Zaytun, which has been established for 25 years, is committed to becoming an educational center that promotes tolerance and peace, by combining Indonesian traditions with modern education. This research aims to determine the culture of tolerance and peace in Al-Zaytun as the basis for national and state life based on Pancasila. The research method used is literature study, using an analytical description approach. The results show that Al-Zaytun is committed to developing student characters that reflect the values of Pancasila, by combining traditional and modern principles. In addition, education at Al-Zaytun also emphasizes the importance of tolerance, social justice, and national spirit, in line with national education goals. Thus, Al-Zaytun plays an important role in developing a culture of tolerance and peace and strengthening the values of Pancasila in society. Keywords: Tolerance, Peace, Pancasila, Ma'had Al-Zaytun